A kind of high strength asphalt concrete and preparation method thereof

By introducing cellulose ester derivatives and modified asphalt into asphalt concrete and optimizing the component distribution ratio, the problem of insufficient mechanical properties of existing asphalt concrete is solved, significantly improving its mechanical properties and high temperature resistance, and extending the service life of pavement materials.

CN119263702BActive Publication Date: 2025-03-04HANDAN GUANGTAI HIGHWAY ENG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411813251.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-04
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing asphalt concrete has insufficient mechanical properties under high-strength vehicle loads and extreme climatic conditions, and is prone to cracks, ruts and local collapses, which affects the quality and service life of the road surface.

Method used

A high-strength asphalt concrete is used, and its components include 18 to 24 parts of asphalt, 8 to 16 parts of cement, 80 to 100 parts of gravel, 20 to 30 parts of cellulose ester derivatives, 40 to 50 parts of medium sand and 50 to 60 parts of mineral fine powder. Its mechanical properties and high temperature resistance are improved by modifying asphalt and specific group distribution ratios.

Benefits of technology

It significantly improves the mechanical properties and high temperature resistance of asphalt concrete, can more effectively support high-strength vehicle loads and resist extreme climatic conditions, and extend the service life of road materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and proposes a high-strength asphalt concrete and a preparation method thereof. The asphalt concrete comprises the following components in parts by weight: 18 to 24 parts of asphalt, 8 to 16 parts of cement, 80 to 100 parts of crushed stone, 20 to 30 parts of cellulose ester derivatives, 40 to 50 parts of medium sand, and 50 to 60 parts of mineral fine powder; the cellulose ester derivatives include cellulose acetate phthalate and cellulose acetate, and the weight ratio of cellulose acetate phthalate to cellulose acetate is 1:9 to 9:1. Through the above technical scheme, the problem of poor mechanical properties of asphalt concrete in the related art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to a high-strength asphalt concrete and a preparation method thereof. Background Art

[0002] With the continuous advancement of my country's transportation engineering technology, the performance requirements for asphalt pavement materials are becoming increasingly stringent. As a pavement material, it must have good mechanical properties to effectively support vehicle loads and other external forces, thereby extending the service life of the pavement material. Traditional asphalt pavement materials are mainly based on asphalt, but there are some inherent limitations in terms of mechanical strength, especially under high-intensity traffic loads and extreme climatic conditions. These problems are more prominent and may cause cracks, rutting, and local collapse in the pavement.

[0003] In order to overcome these defects, asphalt concrete is currently often used as a pavement material. Asphalt concrete, commonly known as asphalt concrete, is made by mixing artificially selected mineral materials with specific gradations (such as crushed stone, crushed gravel), stone chips or sand, mineral powder, etc. with a certain proportion of road asphalt. Although asphalt concrete has improved mechanical properties compared to traditional asphalt pavement materials, its performance still needs to be further improved under high-intensity vehicle loads. Long-term external force loads may still cause the pavement's bearing capacity to decrease, forming deformations such as rutting.

[0004] Therefore, the mechanical property defects of asphalt concrete have become a key factor affecting the quality and service life of the pavement. The development of an asphalt concrete with excellent mechanical properties is of great significance to improving the overall performance of pavement materials. Summary of the invention

[0005] The invention provides a high-strength asphalt concrete and a preparation method thereof, which solves the problem of poor mechanical properties of asphalt concrete in the related art.

[0006] The technical solution of the present invention is as follows:

[0007] The present invention provides a high-strength asphalt concrete, comprising the following components in parts by weight:

[0008] 18-24 parts of asphalt, 8-16 parts of cement, 80-100 parts of crushed stone, 20-30 parts of cellulose ester derivatives, 40-50 parts of medium sand, 50-60 parts of mineral fine powder;

[0009] The cellulose ester derivatives include cellulose acetate phthalate and cellulose acetate, and the weight ratio of the cellulose acetate phthalate to the cellulose acetate is 1:9-9:1.

[0010] As a further technical solution, the weight ratio of the cellulose acetate phthalate to cellulose acetate is 2-5:1.

[0011] When the weight ratio of cellulose acetate phthalate and cellulose acetate is 2~5:1, the mechanical properties of asphalt concrete can be further improved.

[0012] As a further technical solution, the asphalt is modified asphalt, and the raw materials of the modified asphalt include asphalt and aluminum borate whiskers.

[0013] In the present invention, the asphalt is modified asphalt. The asphalt is modified by using aluminum borate whiskers, which can enhance the internal structural stability of the asphalt while reducing the sensitivity of the asphalt to temperature, making it less likely to deform at high temperatures, thereby improving the high temperature resistance of the asphalt concrete.

[0014] As a further technical solution, the weight ratio of the asphalt to the aluminum borate whisker is 10:1~2.

[0015] When the weight ratio of asphalt and aluminum borate whiskers is 10:1~2, the high temperature resistance of asphalt concrete can be further improved.

[0016] As a further technical solution, the preparation method of the modified asphalt comprises the following steps: heating the asphalt, adding the aluminum borate whiskers, and mixing them evenly to obtain the modified asphalt.

[0017] As a further technical solution, during the heating, the temperature is 155-175°C.

[0018] As a further technical solution, the aluminum borate whisker is 5-acetylsalicylic acid amide modified aluminum borate whisker; the 5-acetylsalicylic acid amide modified aluminum borate whisker is obtained by modifying aluminum borate whisker with 5-acetylsalicylic acid amide.

[0019] In the present invention, the inventors found that the surface of aluminum borate whiskers was modified by 5-acetylsalicylicamide, and after the modified aluminum borate whiskers were added to asphalt, the high temperature resistance of asphalt concrete could be further improved. The reason may be that after the aluminum borate whiskers were modified by 5-acetylsalicylicamide, the binding effect between the aluminum borate whiskers and asphalt could be improved, thereby improving the modification effect of the aluminum borate whiskers on asphalt, and further improving the high temperature resistance of asphalt concrete.

[0020] As a further technical solution, the weight ratio of the aluminum borate whiskers to 5-acetylsalicylicylamide is 8:1-3.

[0021] When the weight ratio of aluminum borate whiskers to 5-acetylsalicylicamide is 8:1~3, by reasonably adjusting the weight ratio of the two, the modification effect of aluminum borate whiskers on asphalt can be optimized, thereby further improving the high temperature resistance of asphalt concrete.

[0022] As a further technical solution, the preparation method of the 5-acetylsalicylicamide modified aluminum borate whisker comprises the following steps: adding the aluminum borate whisker into ethanol, adding the 5-acetylsalicylicamide, dispersing evenly, and drying to obtain the 5-acetylsalicylicamide modified aluminum borate whisker.

[0023] As a further technical solution, the crushed stone is one or more of basalt crushed stone, gravel crushed stone, dolomite crushed stone, and diabase crushed stone.

[0024] As a further technical solution, the crushed stone includes basalt crushed stone and dolomite crushed stone; the weight ratio of the basalt crushed stone to the dolomite crushed stone is 1:1.

[0025] As a further technical solution, the particle size of the crushed stone is 25~35mm.

[0026] As a further technical solution, the medium sand is one or more of medium quartz sand, medium basalt sand, and medium garnet sand, preferably medium quartz sand.

[0027] As a further technical solution, the particle size of the medium sand is 0.25~0.5mm.

[0028] As a further technical solution, the mineral fine powder is one or more of fly ash, potassium feldspar powder, and talcum powder.

[0029] As a further technical solution, the mineral fine powder includes fly ash and talcum powder; the weight ratio of the fly ash to the talcum powder is 1:1.

[0030] As a further technical solution, the particle size of the mineral fine powder is 30-100 μm.

[0031] The present invention also proposes a method for preparing the high-strength asphalt concrete, comprising the following steps:

[0032] S1, mixing the cement, crushed stone, medium sand and mineral fine powder in parts by weight to obtain a mixture;

[0033] S2. Performing a first heating of the asphalt of the components in parts by weight, after heat preservation, adding the mixture, mixing evenly, adding the cellulose ester derivative, performing a second heating, stirring, and cooling to obtain the asphalt concrete.

[0034] As a further technical solution, in step S2, during the first heating, the heating temperature is increased to 155-175°C and kept warm for 30-40 minutes; during the second heating, the heating temperature is increased to 130-140°C; during the stirring, the stirring speed is 1200-1400 r / min and the stirring time is 20-30 minutes; during the cooling, the cooling temperature is decreased to 70-80°C.

[0035] The working principle and beneficial effects of the present invention are:

[0036] In the present invention, asphalt concrete includes asphalt, cellulose ester derivatives, cement, crushed stone, medium sand, and mineral fine powder. Under the effective coordination of various components, asphalt concrete with stable internal structure can be formed, and it has excellent mechanical properties and high temperature resistance. Among them, cellulose ester derivatives are introduced into asphalt concrete, specifically including cellulose acetate phthalate and cellulose acetate. Through the synergistic use of these two cellulose ester derivatives, various fillers in the mixture can be distributed more evenly, and they can have good compatibility with asphalt, and asphalt concrete with a dense and stable structure can be formed, thereby significantly improving the mechanical properties of asphalt concrete. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the following embodiments and comparative examples, asphalt is petroleum asphalt, model 10#; cement is ordinary Portland cement, model PO 42.5; the model of cellulose acetate phthalate is l12585, and the manufacturer is Wuhan Kemik Biomedical Technology Co., Ltd.; the model of cellulose acetate is 132E050; the particle size of basalt crushed stone is 30 mm; the particle size of dolomite crushed stone is 30 mm; the particle size of quartz sand is 0.5 mm; the particle size of fly ash is 44 μm; the particle size of talc is 44 μm; the average diameter of aluminum borate whiskers is 1.5 μm, and the average length is 35 μm.

[0039] Example 1

[0040] A high-strength asphalt concrete comprises the following components in parts by weight:

[0041] 18 parts asphalt, 8 parts cement, 80 parts crushed stone, 20 parts cellulose ester derivatives, 40 parts quartz sand, 50 parts mineral fine powder;

[0042] Cellulose ester derivatives include 2 parts of cellulose acetate phthalate and 18 parts of cellulose acetate;

[0043] The crushed stone includes 40 parts of basalt crushed stone and 40 parts of dolomite crushed stone;

[0044] Mineral fine powder includes 25 parts fly ash and 25 parts talc;

[0045] The method for preparing asphalt concrete comprises the following steps:

[0046] S1, mixing the above-mentioned components in parts by weight of cement, crushed stone, quartz sand, and mineral fine powder uniformly to obtain a mixture;

[0047] S2. Heat the asphalt of the above-mentioned components by weight to 155°C for the first time, keep it warm for 40 minutes, add the mixture, mix well, add cellulose ester derivatives, heat it to 130°C for the second time, stir at a stirring speed of 1200 r / min for 30 minutes, cool it to 70°C, and obtain asphalt concrete.

[0048] Example 2

[0049] A high-strength asphalt concrete comprises the following components in parts by weight:

[0050] 20 parts asphalt, 12 parts cement, 90 parts crushed stone, 24 parts cellulose ester derivatives, 45 parts quartz sand, 56 parts mineral fine powder;

[0051] The cellulose ester derivative comprises 14 parts of cellulose acetate phthalate and 10 parts of cellulose acetate;

[0052] The crushed stone includes 45 parts of basalt crushed stone and 45 parts of dolomite crushed stone;

[0053] The mineral fine powder includes 28 parts of fly ash and 28 parts of talc;

[0054] The method for preparing asphalt concrete comprises the following steps:

[0055] S1, mixing the above-mentioned components in parts by weight of cement, crushed stone, quartz sand, and mineral fine powder uniformly to obtain a mixture;

[0056] S2. Heat the asphalt of the above-mentioned components in parts by weight to 165°C for the first time, keep it warm for 35 minutes, add the mixture, mix well, add cellulose ester derivatives, heat it to 135°C for the second time, stir at a stirring speed of 1300 r / min for 25 minutes, cool it to 75°C, and obtain asphalt concrete.

[0057] Example 3

[0058] A high-strength asphalt concrete comprises the following components in parts by weight:

[0059] 24 parts asphalt, 16 parts cement, 100 parts crushed stone, 30 parts cellulose ester derivatives, 50 parts quartz sand, 60 parts mineral fine powder;

[0060] The cellulose ester derivatives include 27 parts of cellulose acetate phthalate and 3 parts of cellulose acetate;

[0061] The crushed stone includes 50 parts of basalt crushed stone and 50 parts of dolomite crushed stone;

[0062] The mineral fine powder includes 30 parts of fly ash and 30 parts of talc;

[0063] The method for preparing asphalt concrete comprises the following steps:

[0064] S1, mixing the above-mentioned components in parts by weight of cement, crushed stone, quartz sand, and mineral fine powder uniformly to obtain a mixture;

[0065] S2. Heat the asphalt of the above-mentioned components by weight to 175°C for the first time, keep it warm for 30 minutes, add the mixture, mix well, add cellulose ester derivatives, heat it to 140°C for the second time, stir at a stirring speed of 1400r / min for 20 minutes, cool it to 80°C, and obtain asphalt concrete.

[0066] Example 4

[0067] The only difference between this embodiment and embodiment 2 is that in this embodiment, the cellulose ester derivative includes 21 parts of cellulose acetate phthalate and 3 parts of cellulose acetate.

[0068] Example 5

[0069] The only difference between this embodiment and embodiment 2 is that in this embodiment, the cellulose ester derivative includes 16 parts of cellulose acetate phthalate and 8 parts of cellulose acetate.

[0070] Example 6

[0071] The only difference between this embodiment and embodiment 2 is that in this embodiment, the cellulose ester derivative includes 20 parts of cellulose acetate phthalate and 4 parts of cellulose acetate.

[0072] Example 7

[0073] The only difference between this embodiment and embodiment 6 is that in this embodiment, the asphalt is modified asphalt, and its preparation method includes the following steps: after heating 20 parts of asphalt to 165° C., adding 1 part of aluminum borate whisker, mixing evenly, to obtain modified asphalt.

[0074] Example 8

[0075] The only difference between this embodiment and embodiment 7 is that in this embodiment, 20 parts of asphalt and 5 parts of aluminum borate whiskers are added.

[0076] Example 9

[0077] The only difference between this embodiment and embodiment 7 is that in this embodiment, 20 parts of asphalt and 2 parts of aluminum borate whiskers are added.

[0078] Example 10

[0079] The only difference between this embodiment and embodiment 7 is that in this embodiment, 20 parts of asphalt and 4 parts of aluminum borate whiskers are added.

[0080] Embodiment 11

[0081] The only difference between this embodiment and embodiment 10 is that in this embodiment, the aluminum borate whisker is 5-acetylsalicylicamide modified aluminum borate whisker, and its preparation method comprises the following steps: after adding 4 parts of aluminum borate whisker to 10 parts of ethanol, adding 0.2 parts of 5-acetylsalicylicamide, dispersing evenly, and drying to obtain 5-acetylsalicylicamide modified aluminum borate whisker.

[0082] Example 12

[0083] The only difference between this embodiment and embodiment 10 is that in this embodiment, 4 parts of aluminum borate whiskers and 1.7 parts of 5-acetylsalicylic acid amide are added.

[0084] Embodiment 13

[0085] The only difference between this embodiment and embodiment 10 is that in this embodiment, 4 parts of aluminum borate whiskers and 0.5 parts of 5-acetylsalicylic acid amide are added.

[0086] Embodiment 14

[0087] The only difference between this embodiment and embodiment 10 is that in this embodiment, 4 parts of aluminum borate whiskers and 1.5 parts of 5-acetylsalicylic acid amide are added.

[0088] Comparative Example 1

[0089] The only difference between this comparative example and Example 1 is that in this comparative example, the cellulose ester derivative includes only 20 parts of cellulose acetate phthalate.

[0090] Comparative Example 2

[0091] The only difference between this comparative example and Example 1 is that in this comparative example, the cellulose ester derivative includes only 20 parts of cellulose acetate.

[0092] Comparative Example 3

[0093] The only difference between this comparative example and Example 1 is that in this comparative example, no cellulose ester derivative is added.

[0094] Experimental Example 1 Mechanical Properties Test

[0095] The asphalt concrete samples prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were placed in a 60°C oven and cured for 24 hours. The following performance tests were performed in accordance with GB / T 50784-2013 Technical Standard for On-site Inspection of Concrete Structures:

[0096] Compressive strength: The compressive strength of asphalt concrete samples was tested according to the method in GB / T 50784-2013 Technical Standard for On-site Inspection of Concrete Structures. The size of the concrete sample was 150mm×150mm×150mm. The test result was the average value of three samples, and the result was accurate to 0.1MPa.

[0097] Flexural strength: The flexural strength of asphalt concrete specimens was tested according to the method in GB / T 50784-2013 Technical Standard for On-site Inspection of Concrete Structures. The size of the asphalt concrete specimens was 100mm×100mm×400mm. The test results were the average of three specimens, and the results were accurate to 0.1MPa.

[0098] The test results are shown in Table 1 below:

[0099] Table 1 Mechanical properties test results of Examples 1 to 6 and Comparative Examples 1 to 3

[0100]

[0101] In Table 1, compared with comparative examples 1 to 3, the compressive strength and flexural strength of the asphalt concrete prepared in Example 1 are significantly improved, indicating that when cellulose ester derivatives, specifically including cellulose acetate phthalate and cellulose acetate, are introduced into the asphalt concrete, the two have a synergistic effect and can significantly improve the mechanical properties of the asphalt concrete.

[0102] Compared with Examples 2 and 4, the compressive strength and flexural strength of the asphalt concrete prepared in Examples 5-6 are improved, indicating that when the weight ratio of cellulose acetate phthalate and cellulose acetate is 2-5:1, the mechanical properties of the asphalt concrete can be further improved.

[0103] Experimental Example 2 High temperature resistance test

[0104] The asphalt concrete samples prepared in Examples 6 to 14 were placed in a 60°C oven and cured for 24 hours, and then the following performance tests were performed according to the method in JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering":

[0105] High temperature rutting dynamic stability: According to the method in JTG E20-2011 "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering", the high temperature rutting dynamic stability test was carried out on the asphalt concrete specimens, where the size of the asphalt concrete specimens was 300mm×300mm×50mm, the test temperature was 60℃, the wheel pressure was 0.7MPa, the total load was 780N, and the test result was the average value of 3 specimens;

[0106] Marshall stability: Marshall stability test was carried out on asphalt concrete specimens according to the method in JTG E20-2011 "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering". Three specimens were taken. The specimens were cylindrical specimens with a diameter of 101.6 mm and a height of 63.5 mm. The specimen temperature was 60°C and the loading speed was 50 mm / min. The test result was the average value of the three specimens, and the result was accurate to 0.1 kN.

[0107] The test results are shown in Table 2 below:

[0108] Table 2 High temperature resistance test results of Examples 6 to 14

[0109]

[0110] In Table 2, compared with Example 6, the high-temperature rutting dynamic stability and Marshall stability of the asphalt concrete prepared in Examples 7 to 10 are improved, indicating that when the asphalt is modified asphalt, the high-temperature resistance of the asphalt concrete can be improved by modifying the asphalt with aluminum borate whiskers. Compared with Examples 7 to 8, the high-temperature rutting dynamic stability and Marshall stability of the asphalt concrete prepared in Examples 9 to 10 are improved, indicating that when the weight ratio of asphalt to aluminum borate whiskers is 10:1 to 2, the high-temperature resistance of the asphalt concrete can be further improved.

[0111] Compared with Example 10, the high-temperature rutting dynamic stability and Marshall stability of the asphalt concrete prepared in Examples 11 to 14 are improved, indicating that the surface modification of aluminum borate whiskers by 5-acetylsalicylicamide and the addition of the modified aluminum borate whiskers to asphalt can further improve the high-temperature resistance of asphalt concrete. Among them, compared with Examples 11 to 12, the high-temperature rutting dynamic stability and Marshall stability of the asphalt concrete prepared in Examples 13 to 14 are improved, indicating that when the weight ratio of aluminum borate whiskers to 5-acetylsalicylicamide is 8:1 to 3, by reasonably adjusting the weight ratio of the two, the modification effect of aluminum borate whiskers on asphalt can be optimized, thereby further improving the high-temperature resistance of asphalt concrete.

[0112] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength asphalt concrete, characterized in that: The composition comprises the following components in parts by weight: 18-24 parts of asphalt, 8-16 parts of cement, 80-100 parts of crushed stone, 20-30 parts of cellulose ester derivatives, 40-50 parts of medium sand, 50-60 parts of mineral fine powder; The cellulose ester derivatives include cellulose acetate phthalate and cellulose acetate, and the weight ratio of the cellulose acetate phthalate to the cellulose acetate is 1:9-9:

1.

2. The high-strength asphalt concrete according to claim 1, characterized in that: The weight ratio of the cellulose acetate phthalate to cellulose acetate is 2-5:

1.

3. The high-strength asphalt concrete according to claim 1, characterized in that: The asphalt is modified asphalt, and the raw materials of the modified asphalt include asphalt and aluminum borate whiskers.

4. The high-strength asphalt concrete according to claim 3, characterized in that: The weight ratio of the asphalt to the aluminum borate whisker is 10:1-2.

5. The high-strength asphalt concrete according to claim 3, characterized in that: The preparation method of the modified asphalt comprises the following steps: heating the asphalt, adding the aluminum borate whisker, and mixing evenly to obtain the modified asphalt.

6. The high-strength asphalt concrete according to claim 3, characterized in that: The aluminum borate whisker is 5-acetylsalicylic acid amide modified aluminum borate whisker; the 5-acetylsalicylic acid amide modified aluminum borate whisker is obtained by modifying the aluminum borate whisker with 5-acetylsalicylic acid amide.

7. The high-strength asphalt concrete according to claim 6, characterized in that: The weight ratio of the aluminum borate whisker to 5-acetylsalicylic acid amide is 8:1-3.

8. The high-strength asphalt concrete according to claim 6, characterized in that: The preparation method of the 5-acetylsalicylic acid amide modified aluminum borate whisker comprises the following steps: adding the aluminum borate whisker into ethanol, adding the 5-acetylsalicylic acid amide, dispersing evenly, and drying to obtain the 5-acetylsalicylic acid amide modified aluminum borate whisker.

9. The high-strength asphalt concrete according to claim 1, characterized in that: The crushed stone is one or more of basalt crushed stone, gravel crushed stone, dolomite crushed stone, diabase crushed stone; and / or The medium sand is one or more of quartz sand, basalt sand, and garnet sand; and / or The mineral fine powder is one or more of fly ash, potassium feldspar powder and talc powder.

10. The method for preparing high-strength asphalt concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing the cement, crushed stone, medium sand and mineral fine powder in parts by weight to obtain a mixture; S2. Performing a first heating of the asphalt of the components in parts by weight, after heat preservation, adding the mixture, mixing evenly, adding the cellulose ester derivative, performing a second heating, stirring, and cooling to obtain the asphalt concrete.

Citation Information

Patent Citations

  • High-molecular polymer modified magnesium oxide expanding agent, and preparation method and application thereof

    CN109721273A